Concept of Tawhid-based Science According to Buya A.R. Sutan Mansur - Imron Baehaqi; Saeful Anwar; Abas Mansur Tamam; Ibdalsyah Ibdalsyah (Sekolah Tinggi Agama Islam Taruna Surabaya, 2023)
This study aims to describe the concept of tawhid-based science in the perspective of Buya AR Sutan Mansur. The method used in this research is a type of qualitative research in the form of Library Research by conducting descriptive data analysis. The results of this study found that the concept of science initiated by Buya AR Sutan Mansur is the concept of tawhid-based science, namely the belief in Allah alone, both in the aspects of creation, worship, names and His attributes. In addition, this study also found that Buya AR Sutan Mansur saw the importance of the position of knowledge as the main tool in carrying out all work, especially in implementing the values of tawhid. In addition, he also classified knowledge into two parts, namely the science of belief and the science of ainul belief. Likewise, it was also found about his concept regarding how to obtain knowledge. According to him, knowledge can be obtained through two things, namely through thought and inspiration. In the context of Islamic education, the concept of knowledge of Buya AR Sutan Mansur has a great influence in efforts to achieve the goals of Islamic education, namely to produce students who have faith, devotion and noble character. Buya AR Sutan emphasises the importance of tawhid-based science, because if it is not based on tawhid what happens is damage and decline. According to him, knowledge without tawhid or faith in Allah will cause humans to forget themselves and neglect their obligations and goals in life